2016
DOI: 10.1007/s11746-016-2891-9
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Flavor and Oxidative Stability of Walnut Oil by Microwave Pretreatment

Abstract: Walnut oil is in great demand due to its high nutritional value. However, it is easily oxidized and often loses its typical flavor. This study focused on the role of microwave pretreatment in improving the flavor and oxidative stability of walnut oil, and also investigated the effects of microwave pretreatment on unsaturated fatty acids (oleic, palmitoleic, linoleic, and linolenic acids) and antioxidant components (tocopherols and phytosterols). The results indicate that microwave pretreatment is effective in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 36 publications
(36 reference statements)
1
30
0
1
Order By: Relevance
“…On the other hand, the use of high temperatures of roasting would not be favourable for the walnut flour's antioxidant capacity, as the tannin content could be reduced . On the other hand, the melanoidins formed during roasting have shown some in vitro antioxidant protective effects on lipids, which will be important in preventing oxidative damage of the walnut flour oil . Therefore, melanoidins are probably contributors to the antioxidant activity in the roasted flour samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the use of high temperatures of roasting would not be favourable for the walnut flour's antioxidant capacity, as the tannin content could be reduced . On the other hand, the melanoidins formed during roasting have shown some in vitro antioxidant protective effects on lipids, which will be important in preventing oxidative damage of the walnut flour oil . Therefore, melanoidins are probably contributors to the antioxidant activity in the roasted flour samples.…”
Section: Resultsmentioning
confidence: 99%
“…The production of cold pressed walnut oil is in great demand due to its strong aromatic flavour and high nutritional value . Although pressure systems lead to lower oil recovery, it is the preferred method for obtaining virgin oils with the highest quality .…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in β-sitosterol due to the seeds' thermal pretreatment was also reported in previous studies. Zhou et al [55] reported a 7% decrease in β-sitosterol of walnut oil microwaved at 600 W for 4 min.…”
Section: Phytosterols Compositionmentioning
confidence: 99%
“…The VOCs were analyzed by HS-SPME coupled to GC-MS (7890A-5975C; Agilent Technologies, Santa Clara, CA, U.S.A.) (Zhou, Fan, Chu, & Pei, 2016). Briefly, oil samples (3 mL) were added to 20-mL headspace vials fitted with silicon septa and incubated at 50°C for 10 min.…”
Section: Voc Analysismentioning
confidence: 99%